1994
DOI: 10.1093/brain/117.6.1241
|View full text |Cite
|
Sign up to set email alerts
|

The role of the right hemisphere in the interpretation of figurative aspects of language A positron emission tomography activation study

Abstract: We investigated cerebral activity in six normal volunteers using PET to explore the hypothesis that the right hemisphere has a specific role in the interpretation of figurative aspects of language such as metaphors. We also mapped the anatomical structures involved in sentence comprehension. During regional cerebral blood flow measurement subjects were asked to perform three different linguistic tasks: (i) metaphorical comprehension; (ii) literal comprehension of sentences; and (iii) a lexical-decision task. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

44
320
7
15

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 574 publications
(393 citation statements)
references
References 33 publications
44
320
7
15
Order By: Relevance
“…However, Bottini et al. (1994) compared the activity associated with the comprehension of metaphoric sentences with lexical‐decision tasks; thus, their findings may differ from ours in this study. More recently, Zempleni et al.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…However, Bottini et al. (1994) compared the activity associated with the comprehension of metaphoric sentences with lexical‐decision tasks; thus, their findings may differ from ours in this study. More recently, Zempleni et al.…”
Section: Discussioncontrasting
confidence: 61%
“…However, our present findings were not in agreement with other previous neuroimaging findings (Bottini et al., 1994; Zempleni et al., 2007). Bottini et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least one previous study that directly contrasted narrative-level and sentencelevel comprehension found narrative-specific activation in regions such as ATL, posterior MTG, and DMPFC (Xu et al, 2005). However, other studies have observed greater activation in most of these regions when reading or hearing coherent sentences than random word lists (Bottini et al, 1994;Kuperberg et al, 2000;Stowe et al, 1999;Vandenberghe et al, 2002), suggesting that the difference between narrative-and sentence-level comprehension may be quantitative and not qualitative. Alternatively, narrativespecificity may arise at a hemispheric rather than at a regional level.…”
Section: Introductionmentioning
confidence: 95%
“…Author Manuscript when participants comprehend metaphors, which require distant semantic relations to be noted (Bottini et al, 1994). Also, increased signal occurs in the RH when people generate unusual uses of nouns compared to when they generate the first use that comes to mind, as measured both by ERP (Abdullaev & Posner, 1997) and by fMRI (Seger, Desmond, Glover, & Gabrieli, in press).…”
Section: Author Manuscriptmentioning
confidence: 99%